PENGARUH KETINGGIAN PERANGKAP HAMA LALAT BUAH (Bactrocera sp.) PADA TANAMAN JAMBU BIJI (Psidium Guajava L.) - Sutikno, Agus; Salbiah, Desita; ', Marto (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Guava (Psidium guajava L.) is a tropical plant that comes from southern Mexico and Central America. The rising demand of guava in Indonesia encourages the cultivation of guava which systematically with considerable high economic value. Decreasing productivity of guava currently caused by the attack of fruit flies. Therefore, it is necessary to conduct a research on trapping at several heights. This study uses a randomized block design (RAK) with a height of 0.5 m, 1.5 m and 2.5 m. The results have shown that the effective control of the pest trap fruit flies in the area of guava plant height of 1.5 m is the number of fruit flies were trapped as much as 59.25 flies, the number of male fruit flies were trapped 22.50 flies, female flies were trapped 36, 75 flies and the sex ratio comparison is 1: 1,7. Keywords: Fruit flies, Trap height level, Guava plants.